Distribution of costs and benefits among local stakeholders of Suyac Island Mangrove Ecopark, Brgy. Taba-ao, Sagay City, Negros Occidental. - Montinola, Quenie S.
Mangrove ecosystem is one of the most diverse and highly productive ecosystems but despite the benefits it offers, they are repetitively taken for granted and are highly susceptible to conversion and deforestation. As a result of this, attention of different conservation programs is directed towards aiming to protect and sustain the resource. One conservation technique widely used is community-based ecotourism which aims to conserve the resource while sustaining the well-being of the host population through livelihood. Its success depends on supports the different stakeholders provide to ensure the protection of the area. A disproportionate distribution of cost and benefit among stakeholders can erode their support for the program that could lead to its failure. Thus, this study aims to assess the distribution of costs and benefits among the different local stakeholders of Suyac Island Mangrove Eco-Park in Sagay City, Negros Occidental. Stakeholders were divided into three strata: private, social, and public sector. The costs and benefits of each sector were quantified, distribution among sectors was assessed and net benefits were estimated. Results showed that the primary bearer of cost was the public sector. Despite this, the group earned the highest per capita net benefit. The private sector contrastingly had the highest group net benefit but the least per capita net benefit. The manifested inequality involved in the ecotourism project must be addressed to further improve the program. The total annual benefit of SIME amounted to Php 8,322,299.00. Based on Kaldor-Hicks criterion, a positive net benefit equates that losers were compensated and are still better off relative to their situation prior the establishment of the eco-park.